A Formação de Professores no Curso de Pedagogia - EAD - FACED /UFU (Turma PARFOR, 2011-2015) : foco no ensino de História - Costa, Gelda Gonçalves (2018)
This research had, as general objective, analyze the training of teachers provided by the Distance Education Pedagogy Course of the Federal University of Uberlândia, PARFOR (National Plan for the Training of Teachers of Elementary Level) Group (2011-2015), evidencing the teaching of History. Specifically, we chose the following objectives: i - To present the process of implementing Distance Education at UFU - Uberlândia / MG / Brazil; ii - To analyze the Pedagogy course in mode of the Federal University of Uberlândia, through the Pedagogical Project of the Course - PPC, evidencing the course carried out by the PARFOR group (2011 - 2015); iii - Reflect on the possible contributions of the Pedagogy Course DAA PARFOR (2011-2015) in the process of teaching History in the initial years of elementary school. In order to achieve the objectives proposed in this study, we used bibliographic reviews and analysis of documents and narratives of the course participants. Considering that the training of PARFOR Class teachers took place in the distance education modality, in the first moment of the research priority was given to relevant aspects such as the historical process of implementing this modality of education in a globalized way in Brazil and the process of implementing Distance Education in UFU. In the second moment, the Course of Pedagogy of the FACED / UFU was analyzed in this modality of education through the Pedagogical Proposal of the Course and reflections about the contributions of this course in the training of teachers to teach history for the initial years of elementary level. Finally, we attempt to demonstrate the impacts on the training of the teachers collaborating in the research, through the presentation of the place of the History discipline in the different official documents, the analysis of the Methodology Teaching History Guide, concomitantly with the analysis of the narratives of 6 teachers collaborating in the research. It was concluded that the Federal University of Uberlândia - UFU has the potential to offer distance education in higher education. The course includes teachers who need higher education in service provided for in Law of Guidelines and Bases for Education (LDB / 1996). It has also been shown that despite the quality of the teaching of the PARFOR Class Pedagogic course, there is still a fragility to be overcome: the dichotomy between theory and practice. The narratives of the collaborating teachers revealed that the contributions of the Course in the process of teaching and learning History in the early years of elementary school were fragile. This can be understood by the time devoted to the discipline of the PPC concerning the teaching of History (contents and methodologies) that is restricted and challenging in order to train teachers capable of producing knowledge and pedagogical practices that are significant for historical learning. The didactic material produced, Guide to Methodology Teaching History, meets the record of the discipline. The organization of the material can aid in the understanding of the historiographic movement that marked the history of the teaching of History in general scope. We consider the importance of potentializing the uses of the Moodlle Platform in terms of the possibilities of conducting dialogues among the students, since the process of teaching and learning history requires dialogue and exchange of experiences. Keywords: Distance Education. Teacher training. Teaching History.